Preparation method of modified superfine quartz powder
Through the comprehensive methods of dispersion modification, curing modification, activation modification and fluidization crushing, combined with composite dispersant technology, the problems of uneven particle size, high impurity content and poor dispersion of ultrafine quartz powder are solved, and the particle size is prepared. Modified ultrafine quartz powder with uniformity, high purity and good compatibility with polymers, meets the high frequency, high speed, thin and small-scale needs of electronic materials such as copper clad plates.
Patent Information
- Application Number
- CN202411174632.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-26
- Publication Date
- 2024-12-13
AI Technical Summary
The existing ultrafine quartz powder preparation technology has problems such as uneven particle size, high impurity content, poor dispersion and poor compatibility. It is difficult to meet the requirements for dielectric properties and purity in electronic materials such as copper clad plates. The development needs of high frequency, high speed and lightweight miniaturization.
Using a comprehensive method of dispersion modification, curing modification, activation modification and fluidization crushing, ultrafine quartz particles are wrapped in liquid film form through ultrasonic wave, heating, microwave excitation and supersonic jet flow technologies, combined with composite dispersant, to form ultrafine quartz particles The organically modified layer enhances the hydrophobicity and dispersion of particles, avoids agglomeration and impurities adsorption, and achieves improved particle size uniformity and purity.
Prepare modified ultrafine quartz powder with uniform particle size, low impurity content and good compatibility with polymers, which improves dielectric properties and conductivity, and meets the high frequency, high speed and lightweight and miniaturization needs of electronic materials such as copper clad plates. .
Smart Images

Figure BDA0005010378140000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of non-metallic mineral powder processing, and in particular to a method for preparing modified ultrafine quartz powder. Background Art
[0002] Quartz powder is a non-metallic powder obtained by crushing and grinding natural quartz ore. Quartz powder with a particle size of D97≤10um can be called ultrafine quartz powder. The existing ultrafine quartz powder preparation technology on the market mostly uses ball mills, vibration mills, Raymond mills and other grinding equipment to repeatedly grind quartz ore, which has the following problems:
[0003] (1) The product is uneven, with a wide and uneven particle size distribution. The finest particle can be less than 10μm, but the overall particle size is coarse, and the maximum particle size even exceeds 20-30μm.
[0004] (2) The grinding process introduces a lot of impurities. The grinding equipment uses iron balls or steel balls as grinding media. The collision and friction between them and the quartz particles and the inner wall of the equipment easily introduce very fine iron impurities, which are not easy to remove.
[0005] (3) During the grinding process, the powder is prone to adsorb impurity particles and water vapor in the air due to surface energy or static electricity, forming agglomerates.
[0006] Copper clad laminate is an important substrate for the production of printed circuit boards (PCBs). It directly affects the performance of integrated circuits. In practical applications, related materials used in copper clad laminates have high electrical performance requirements. Resin and quartz powder are two important raw materials for copper clad laminates, and the two are pressed into shape by adhesives. As the copper clad laminate industry gradually develops in the direction of high frequency, high speed, lightness, and miniaturization, copper clad laminates with certain requirements for dielectric properties and dielectric loss require quartz powder raw materials with finer particle size (to improve substrate strength), higher purity (to improve dielectric properties) and narrower particle size range (uniform).
[0007] When used in copper-clad laminates and other electronic materials, the conductive elements such as copper, iron, and aluminum in quartz powder have a great influence on the conductive and dielectric properties of downstream finished products, so quartz powder is required to have a high purity. Quartz powder is an inorganic material with a highly hydrophilic surface, while the resin base material, as a high molecular polymer, has a large difference in surface properties from quartz powder. The mixing of the two requires solving the problems of compatibility and particle dispersion, so the surface modification of ultrafine quartz powder is required.
[0008] The existing quartz powder modification methods mainly include the following methods:
[0009] (1) Dry modification: First, prepare ultrafine quartz powder separately, then add a certain proportion of modifier to the quartz powder and mix vigorously to achieve modification.
[0010] (2) Wet modification: First, prepare ultrafine quartz powder separately, then adjust the quartz powder into emulsion or slurry, and perform strong mixing to achieve modification.
[0011] (3) Combination of dry and wet methods: First, prepare ultrafine quartz powder separately, (generally) first perform dry modification, and then perform wet modification.
[0012] The above methods all modify the powder after preparation. In the dry modification, the quartz powder has already undergone agglomeration and physical adsorption before modification, so the overall modification is uneven, which affects the dispersibility and compatibility in polymers. Wet modification requires strict selection of modifiers. The modifier must be a chemical reagent with good water solubility (good water solubility can better disperse and combine with Si-OH groups), and it needs to be dehydrated. It has certain requirements on the particle size range of quartz powder. When the amount of modifier is too large, the modified ultrafine quartz powder will produce multi-layer adsorption, and a weak layer will be formed at the interface between the quartz powder and the organic polymer, resulting in the inability to play the bridge role of a single molecule. When the powder particle size is extremely fine (less than 5 microns), the drying cycle is relatively long. Method 3 combines the advantages of dry and wet modification, and the modification effect is better than single modification, but its modification path becomes longer and the process becomes complicated, and it still cannot solve the problem of multi-layer adsorption. Summary of the invention
[0013] The object of the present invention is to provide a method for preparing modified ultrafine quartz powder. The prepared quartz powder has high particle size uniformity, low impurity content, and good dispersibility and compatibility with high molecular polymers.
[0014] The above technical objectives of the invention are achieved through the following technical solutions:
[0015] A method for preparing modified ultrafine quartz powder comprises the following steps:
[0016] Step S1, dispersion modification, after washing 200-300 mesh quartz sand with water, adding a dispersion modifier, mixing evenly, then adding it to an ultrasonic disperser, treating it in an ultrasonic environment of 20KHZ-30KHZ for 15-30 minutes, to obtain dispersed modified quartz sand;
[0017] Step S2, curing and modification, placing the dispersed modified quartz sand into a heating chamber, keeping the temperature at 95-115° C. for 35-60 minutes;
[0018] Step S3, activation and modification, placing the quartz sand treated in step S2 in a pressure-maintaining hot field at an ambient temperature of 450-600° C., and introducing chlorine gas therein for 5-15 seconds to obtain activated modified quartz sand;
[0019] Step S4, fluidized crushing and modification, adding the activated modified quartz sand into the crushing chamber, accelerating the activated modified quartz sand by a supersonic jet flow, forming a centripetal reverse jet flow field at the lower part of the crushing chamber, and forming a particle flow of the activated modified quartz sand under the action of the pressure difference, and crushing the activated modified quartz sand by the collision and friction of multiple particle flows to form ultrafine quartz particles; at the same time, spraying a composite dispersant into the crushing chamber through a liquid atomizing nozzle, so that the composite dispersant wraps the surface of the ultrafine quartz particles in the form of a liquid film, and obtaining the modified ultrafine quartz powder after air drying.
[0020] Through the above technical scheme, after the humidified quartz sand is mixed and dispersed and modified, the dispersion modifier is combined with the Si-OH group on the surface of the quartz sand through water as a medium, and under the action of high temperature, through hydrolysis, condensation, hydrogen bonding, covalent bonding and other chemical reaction processes, a surface hydrophobic and organic modified monolayer is formed on the surface of the quartz sand, thereby avoiding the agglomeration phenomenon caused by the adsorption of charged particles on the surface of the quartz sand during the purification and modification of the quartz sand, thereby making the quartz sand particles have good fluidity during the purification and modification, ensuring the purification effect; at the same time, under the action of ultrasound, the surface of the quartz sand is mechanically activated, and the high temperature and impact force generated by the cavitation bubbles in the quartz sand at the moment of quenching produce active sites and active groups on the surface of the quartz sand, thereby increasing the The reaction contact area during purification and modification is increased, thereby effectively enhancing the purification and modification effect of quartz sand; further, the activated modified quartz sand is accelerated by a supersonic jet flow, and the activated modified quartz sand is crushed by the collision and friction of multiple particle flows to form ultrafine quartz particles. There is no loss during the processing process, and no new impurities are introduced. Since the quartz particles are brittle, the size of the particles rapidly decreases after friction and collision with each other, and the sharp edges and corners become less, and the roundness of the particles is further improved. During crushing, the composite dispersant is sprayed into the crushing chamber through a liquid atomizing nozzle at the same time, so that the composite dispersant wraps the surface of the ultrafine quartz particles in the form of a liquid film, so that the composite dispersant can be well combined with the active sites on the surface of the quartz powder particles, thereby effectively improving the dispersibility of the quartz powder particles.
[0021] Preferably, the composite dispersant comprises water, n-octanol, polyethylene glycol and phenothiazine; wherein the content of n-octanol is 17-41wt%, the content of polyethylene glycol is 26-35wt%, and the content of phenothiazine is 3-5wt%.
[0022] Through the above technical scheme, quartz sand is a non-polar particle, polyethylene glycol has a strong polarity, and the OH- at both ends of the polyethylene glycol molecular chain can be adsorbed on the surface of the activated modified quartz sand. On this basis, the OH- of n-octanol and the surface OH- of silicon dioxide can undergo a condensation reaction to remove a molecule of water, so that the n-octyl group is grafted onto the surface of the ultrafine quartz particles; through the synergistic effect of polyethylene glycol and n-octanol, the quartz sand particles have good dispersibility, so that the raw materials do not agglomerate or adsorb during the particle crushing process, and the ultrafine powder does not aggregate after production, and has good compatibility with high molecular polymers.
[0023] Preferably, the mass ratio of the added amount of the dispersion modifier to the quartz sand is (3-5):1000; the dispersion modifier includes γ-methacryloxypropyltrimethoxysilane and titanate, and the mass ratio of γ-methacryloxypropyltrimethoxysilane to titanate is 4:1.
[0024] Through the above technical scheme, γ-methacryloxypropyltrimethoxysilane and titanate are used together, and the titanate enhances the coupling effect of the silane coupling agent, promotes the functional groups on the silane coupling agent to combine with the OH- on the surface of the quartz sand, and finally forms a modified monolayer; after dispersion modification and curing modification, the dispersibility of the quartz sand is effectively improved, and the adsorption performance of impurities and fine dust is greatly reduced; in the activation modification process, because the quartz sand particles are not easy to agglomerate and have good dispersibility, there is no need to apply mechanical dispersion or air flow dispersion to the quartz sand alone to achieve the purpose of uniform activation.
[0025] Preferably, the ambient temperature in the pulverizing chamber is 100-120°C.
[0026] Through the above technical solution, the process of grafting n-octyl to OH- on the surface of quartz powder is an endothermic condensation reaction. The reaction requires a certain temperature as an initial condition, and the OH- adsorption of polyethylene glycol also requires a certain temperature. When the temperature at which n-octanol and polyethylene glycol can react is in the range of 100-120°C, the activity of the reactants increases with the increase in temperature, the molecular thermal motion is intense, the reaction proceeds to the right (forming a modified layer), and the grafting rate increases. At temperatures above 120°C, the hydroxyl groups on the surface of the ultrafine quartz powder will undergo self-condensation, competing with the main reaction, resulting in a decrease in the grafting rate and affecting the modification effect.
[0027] Preferably, in step S3, the pressure-maintaining thermal field adopts a microwave excitation source, and the power of the microwave excitation source is 15KW and the frequency is 2.45GHZ.
[0028] Through the above technical scheme, microwave excitation forms a microwave plasma thermal field and chemical field. The free electrons, ions, active Cl-, free radicals, and uncharged particles generated by microwave excitation collide and react with the siloxane modified layer on the surface of quartz sand, OH- on the surface of quartz sand, and impurity elements such as Fe, Cu, K, and Na to generate low-boiling point volatile chlorides, which are discharged with the exhaust gas, thereby achieving purification and activation of the quartz sand, and providing a large number of grafting sites for the subsequent grafting of siloxane on the surface of ultrafine quartz powder, thereby increasing the binding force of the modified layer. DETAILED DESCRIPTION
[0029] In order to more clearly illustrate the present invention, the invention is further described in detail below in conjunction with the embodiments. It should be understood by those skilled in the art that the following description is an explanation of the invention content, not a limitation, and therefore, the protection scope of the present invention should not be limited thereto.
[0030] Example
[0031] Example 1
[0032] A method for preparing modified ultrafine quartz powder comprises the following steps:
[0033] Step S1, dispersion modification, after washing 200 mesh quartz sand with water, adding a dispersion modifier, mixing evenly, then adding it into an ultrasonic disperser, treating it in a 20KHZ ultrasonic environment for 15 minutes, to obtain dispersion modified quartz sand; the mass ratio of the dispersion modifier added to the quartz sand is 3:1000;
[0034] The dispersion modifier includes gamma-methacryloxypropyltrimethoxysilane and titanate, and the mass ratio of gamma-methacryloxypropyltrimethoxysilane to titanate is 4:1.
[0035] Step S2, curing and modification, putting the dispersed modified quartz sand into a heating chamber and keeping it warm at 95° C. for 35 minutes.
[0036] Step S3, activation and modification, placing the quartz sand treated in step S2 in a pressure-maintaining hot field at an ambient temperature of 450°C, and introducing chlorine gas therein for 5 seconds to obtain activated modified quartz sand; the pressure-maintaining hot field adopts a microwave excitation source, the power of the microwave excitation source is 15KW, and the frequency is 2.45GHZ.
[0037] Step S4, fluidized crushing and modification, adding activated modified quartz sand into the crushing chamber, and the ambient temperature in the crushing chamber is set to 100°C;
[0038] The activated modified quartz sand is accelerated by a supersonic jet flow, and a centripetal reverse jet flow field is formed at the lower part of the pulverizing chamber. Under the action of the pressure difference, the activated modified quartz sand is formed into a particle flow, and the activated modified quartz sand is crushed by the collision and friction of multiple particle flows to form ultrafine quartz particles; at the same time, a composite dispersant is sprayed in the pulverizing chamber through a liquid atomizing nozzle, so that the composite dispersant wraps the surface of the ultrafine quartz particles in the form of a liquid film, and the modified ultrafine quartz powder is obtained after air drying;
[0039] The composite dispersant includes water, n-octanol, polyethylene glycol and phenothiazine; wherein the content of n-octanol is 17wt%, the content of polyethylene glycol is 26wt%, the content of phenothiazine is 3wt%, and the content of water is 54wt%.
[0040] Example 2
[0041] The only difference between Example 2 and Example 1 is that in step S1, the mass ratio of the amount of dispersion modifier added to the quartz sand of 3:1000 is replaced by the mass ratio of the amount of dispersion modifier added to the quartz sand of 5:1000.
[0042] Example 3
[0043] The only difference between Example 3 and Example 1 is that in step S1, the 200-mesh quartz sand that is washed with water and then added with a dispersible modifier is replaced with 300-mesh quartz sand that is washed with water and then added with a dispersible modifier.
[0044] Example 4
[0045] The only difference between Example 4 and Example 1 is that in step S1, the treatment in an ultrasonic environment at 20 kHz for 15 minutes is replaced by the treatment in an ultrasonic environment at 20 kHz for 30 minutes.
[0046] Example 5
[0047] The only difference between Example 5 and Example 1 is that, in step S1, the treatment in an ultrasonic environment at 20 kHz for 15 minutes is replaced by the treatment in an ultrasonic environment at 30 kHz for 15 minutes.
[0048] Example 6
[0049] The only difference between Example 6 and Example 1 is that in step S2, the dispersed modified quartz sand is placed in a heating chamber and kept warm at 115° C. for 35 minutes.
[0050] Example 7
[0051] The only difference between Example 7 and Example 1 is that in step S2, the dispersed modified quartz sand is placed in a heating chamber and kept at 95° C. for 60 minutes.
[0052] Example 8
[0053] The only difference between Example 8 and Example 1 is that in step S3, the quartz sand treated in step S2 is placed in a pressure-maintaining hot field at an ambient temperature of 450°C, and chlorine gas is introduced therein for 15 seconds.
[0054] Example 9
[0055] The only difference between Example 9 and Example 1 is that in step S3, the quartz sand treated in step S2 is placed in a pressure-maintaining hot field at an ambient temperature of 650°C, and chlorine gas is introduced therein for 5 seconds.
[0056] Example 10
[0057] The only difference between Example 10 and Example 1 is that in step S4, the ambient temperature in the pulverizing chamber is 120°C.
[0058] Embodiment 11
[0059] The only difference between Example 11 and Example 1 is that in step S4, the composite dispersant includes water, n-octanol, polyethylene glycol and phenothiazine; wherein the content of n-octanol is 41wt%, the content of polyethylene glycol is 35wt%, the content of phenothiazine is 5wt%, and the content of water is 19wt%.
[0060] Comparative Example
[0061] Comparative Example 1 Dry Modification
[0062] (1) Weigh 50 g of ultrafine quartz powder into a 250 mL three-necked flask and heat to 90 °C in a water bath;
[0063] (2) Preparation of modifier: Use fatty alcohol polyoxyethylene ether (AEO-9) as the modifier, weigh 0.5 of the modifier, add 2 times the weight of water to dissolve and mix evenly;
[0064] (3) Add the prepared modifier while stirring the powder. After the addition is completed, heat it at 90℃.
[0065] The reaction was stirred for 40 min.
[0066] (4) The modified quartz powder is dried in an oven to obtain low-moisture modified ultrafine quartz powder.
[0067] The above method is selected from the Chinese invention patent document with publication number CN115678315A.
[0068] Comparative Example 2 Wet Modification
[0069] The raw material quartz sand is crushed and graded by a jet mill to obtain unmodified primary quartz powder; then, pure water is added to the unmodified primary quartz powder to obtain a slurry, wherein the mass ratio of pure water to unmodified primary silicon micropowder is 1.5:1; the slurry is heated to 110° C., and a mixture of a silane coupling agent and epoxy soybean oil is mixed with the slurry by a spray device for a preliminary modification reaction, wherein the mass ratio of the mixture of the silane coupling agent and the epoxy soybean oil to the slurry is 0.5:1, and the mass ratio of the silane coupling agent to the epoxy soybean oil is 1.5:1;
[0070] After the initial modification reaction is carried out for 5 minutes, a mixture of silane coupling agent and epoxidized soybean oil of the same mass and mixing ratio as in the initial modification reaction is added again using a spray device, and the temperature is continued to be maintained at 110° C. to carry out a secondary modification reaction to obtain a modified material; the modified material is dried to form a filter cake, and finally a jet mill is used to perform ultrafine grinding and classification again to obtain the ultrafine active quartz powder of the present invention.
[0071] The above method is selected from the Chinese invention patent document with publication number CN113004718A.
[0072] Comparative Example 3 Dry-wet composite modification
[0073] 1.5 kg of unmodified ultrafine quartz powder is added to a high-speed mixing modifier, the temperature is set to 140°C, and a pre-hydrolyzed γ-(2,3-epoxypropoxy)propyltrimethoxysilane mixed solution (7.5 g of coupling agent, 7.5 g of ethanol and 15 g of deionized water, the hydrolysis time is 20 min, and the hydrolysis pH is 4.0) is added, and the modification is carried out for 20 min to obtain a first-modified ultrafine quartz powder; 1.5 kg of the first-modified ultrafine quartz powder is added to a wet modifier, and a pre-hydrolyzed N-phenyl-γ-aminopropyltrimethoxysilane mixed solution (7.5 g of coupling agent, 7.5 g of ethanol and 15 g of deionized water, the hydrolysis time is 20 min, and the hydrolysis pH is 7.5) is added, the temperature is set to 80°C, and the modification is carried out for 60 min to obtain a hydrophobic ultrafine quartz powder for epoxy resin.
[0074] The above method is selected from the Chinese invention patent document with authorization announcement number CN113308021B.
[0075] Comparative Example 4
[0076] A method for preparing modified ultrafine quartz powder comprises the following steps:
[0077] Step S1, dispersion modification, after washing 200 mesh quartz sand with water, adding a dispersion modifier, mixing evenly, then adding it into an ultrasonic disperser, treating it in a 20KHZ ultrasonic environment for 15 minutes, to obtain dispersion modified quartz sand; the mass ratio of the dispersion modifier added to the quartz sand is 3:1000;
[0078] The dispersion modifier is γ-aminopropyltriethoxysilane (KH-550).
[0079] Step S2, curing and modification, putting the dispersed modified quartz sand into a heating chamber and keeping it warm at 95° C. for 35 minutes.
[0080] Step S3, activation and modification, placing the quartz sand treated in step S2 in a pressure-maintaining hot field at an ambient temperature of 450°C, and introducing chlorine gas therein for 5 seconds to obtain activated modified quartz sand; the pressure-maintaining hot field adopts a microwave excitation source, the power of the microwave excitation source is 15KW, and the frequency is 2.45GHZ.
[0081] Step S4, fluidized crushing and modification, adding activated modified quartz sand into the crushing chamber, and the ambient temperature in the crushing chamber is set to 100°C;
[0082] The activated modified quartz sand is accelerated by a supersonic jet flow, and a centripetal reverse jet flow field is formed at the lower part of the pulverizing chamber. Under the action of the pressure difference, the activated modified quartz sand is formed into a particle flow, and the activated modified quartz sand is crushed by the collision and friction of multiple particle flows to form ultrafine quartz particles; at the same time, a composite dispersant is sprayed in the pulverizing chamber through a liquid atomizing nozzle, so that the composite dispersant wraps the surface of the ultrafine quartz particles in the form of a liquid film, and the modified ultrafine quartz powder is obtained after air drying;
[0083] The composite dispersant includes water, n-octanol, polyethylene glycol and phenothiazine; wherein the content of n-octanol is 17wt%, the content of polyethylene glycol is 26wt%, the content of phenothiazine is 3wt%, and the content of water is 54wt%.
[0084] Comparative Example 5
[0085] A method for preparing modified ultrafine quartz powder comprises the following steps:
[0086] Step S1, dispersion modification, after washing 200 mesh quartz sand with water, adding a dispersion modifier, mixing evenly, then adding it into an ultrasonic disperser, treating it in a 20KHZ ultrasonic environment for 15 minutes, to obtain dispersion modified quartz sand; the mass ratio of the dispersion modifier added to the quartz sand is 3:1000;
[0087] The dispersion modifier includes gamma-methacryloxypropyltrimethoxysilane and titanate, and the mass ratio of gamma-methacryloxypropyltrimethoxysilane to titanate is 4:1.
[0088] Step S2, curing and modification, putting the dispersed modified quartz sand into a heating chamber and keeping it warm at 95° C. for 35 minutes.
[0089] Step S3, activation and modification, placing the quartz sand treated in step S2 in a pressure-maintaining hot field at an ambient temperature of 450°C, and introducing chlorine gas therein for 5 seconds to obtain activated modified quartz sand; the pressure-maintaining hot field adopts a microwave excitation source, the power of the microwave excitation source is 15KW, and the frequency is 2.45GHZ.
[0090] Step S4, fluidized crushing and modification, adding activated modified quartz sand into the crushing chamber, and the ambient temperature in the crushing chamber is set to 100°C;
[0091] The activated modified quartz sand is accelerated by a supersonic jet flow, and a centripetal reverse jet flow field is formed at the lower part of the pulverizing chamber. Under the action of the pressure difference, the activated modified quartz sand is formed into a particle flow, and the activated modified quartz sand is crushed by the collision and friction of multiple particle flows to form ultrafine quartz particles; at the same time, a composite dispersant is sprayed in the pulverizing chamber through a liquid atomizing nozzle, so that the composite dispersant wraps the surface of the ultrafine quartz particles in the form of a liquid film, and the modified ultrafine quartz powder is obtained after air drying;
[0092] The composite dispersant comprises water, isopropanol and gamma-aminopropyltriethoxysilane (KH-550); wherein the mass ratio of the three is water: isopropanol: gamma-aminopropyltriethoxysilane=2:1:1.
[0093] Test methods
[0094] The quartz powder samples prepared in Examples 1-11 and Comparative Examples 1-5 were respectively subjected to silica content and impurity element detection, particle size distribution detection, oil absorption value detection, and activation index detection.
[0095] Among them, the detection of silicon dioxide content and impurity elements shall be carried out in accordance with the JY-T 0567-2020 experimental standard;
[0096] The particle size distribution is tested according to the GB / T 19077-2016 experimental standard;
[0097] The oil absorption value is tested according to the GB / T 32661-2016 test standard;
[0098] The activation index test was performed according to the following method:
[0099] Weigh 10.00 g of ultrafine powder and place it in a beaker. Add 100 mL of deionized water and stir for 2 minutes, then let it stand until the ultrafine powder completely sinks to the bottom of the water. Remove the powder floating on the water surface, filter, dry and weigh the ultrafine powder that sinks to the bottom of the water.
[0100] The activation index is calculated as:
[0101] Activation index = (10 g - mass of powder settled to the bottom) / 10 g × 100%.
[0102] The test results are shown in Table 1.
[0103]
[0104] Table 1 Test results of examples 1-11 and comparative examples 1-5
[0105] Analysis of the impurity element detection data in Table 1 shows that the method adopted in this scheme has a good effect on the removal of the three main conductive impurity elements of Al, Fe and Cu, while the conventional method has almost no effect on impurity removal;
[0106] Analysis of the particle size distribution test data in Table 1 shows that the D50 and D97 data of the quartz powder prepared by the method adopted in this scheme are effectively reduced compared with the conventional directly crushed quartz powder; and the difference between D50 and D97 is smaller, indicating that the overall particle size is more uniform.
[0107] The larger the oil absorption value, the greater the viscosity of the ultrafine powder in the polymer, the worse the fluidity, and the worse the compatibility with the resin. Therefore, the lower the oil absorption value, the better the compatibility. A high activation index means that the proportion of hydrophobic particles in polar solvents (water is used as the test solvent here) is high, which means that the modification effect of ultrafine powder particles is good and the dispersibility in polar solvents or organic (polymer) systems is good.
[0108] Analysis of the oil absorption value and activation index data in Table 1 shows that the quartz powder prepared by the method adopted in this scheme has a lower oil absorption value than the existing dry method, wet method or dry-wet composite modification method, and the activation index is higher than the existing method, and the activation index is above 90. Comparing the embodiment with comparative examples 4 and 5, after replacing the dispersing modifier and composite dispersant in this scheme with the existing commonly used agent combination, the oil absorption value increases and the activation index decreases, indicating that the modification effect is deteriorated, and the modifier combination in this scheme is better than the existing commonly used combination.
[0109] In summary, the ultrafine quartz powder obtained by the preparation method in this scheme has fine particle size, uniform distribution, high purity, low oil absorption value, high activation index, and the modification effect is better than the commonly used modification process on the market. It has good compatibility with polymers and is easy to disperse.
[0110] Although some specific embodiments of the invention have been described in detail by way of examples, it should be understood by those skilled in the art that the above examples are for illustration only and are not intended to limit the scope of the invention. It should be understood by those skilled in the art that the above embodiments may be modified without departing from the scope and spirit of the invention. The scope of the invention is defined by the appended claims.
Claims
1. A method for preparing modified ultrafine quartz powder, characterized in that: The method comprises the following steps: Step S1, dispersion modification, after washing 200-300 mesh quartz sand with water, adding a dispersion modifier, mixing evenly, then adding it to an ultrasonic disperser, treating it in an ultrasonic environment of 20KHZ-30KHZ for 15-30 minutes, to obtain dispersed modified quartz sand; Step S2, curing and modification, placing the dispersed modified quartz sand into a heating chamber, keeping the temperature at 95-115° C. for 35-60 minutes; Step S3, activation and modification, placing the quartz sand treated in step S2 in a pressure-maintaining hot field at an ambient temperature of 450-600° C., and introducing chlorine gas therein for 5-15 seconds to obtain activated modified quartz sand; Step S4, fluidized crushing and modification, adding activated modified quartz sand into a crushing chamber, accelerating the activated modified quartz sand by a supersonic jet flow, forming a centripetal reverse jet flow field at the lower part of the crushing chamber, and forming a particle flow of the activated modified quartz sand under the action of a pressure difference, and crushing the activated modified quartz sand by collision and friction of multiple particle flows to form ultrafine quartz particles; at the same time, spraying a composite dispersant into the crushing chamber through a liquid atomizing nozzle, so that the composite dispersant wraps the surface of the ultrafine quartz particles in the form of a liquid film, and obtaining the modified ultrafine quartz powder after air drying.
2. The method for preparing modified ultrafine quartz powder according to claim 1, characterized in that: The composite dispersant comprises water, n-octanol, polyethylene glycol and phenothiazine; wherein the content of n-octanol is 17-41wt%, the content of polyethylene glycol is 26-35wt%, and the content of phenothiazine is 3-5wt%.
3. The method for preparing modified ultrafine quartz powder according to claim 1, characterized in that: The mass ratio of the added amount of the dispersing modifier to the quartz sand is (3-5):1000; the dispersing modifier includes γ-methacryloxypropyltrimethoxysilane and titanate, and the mass ratio of the γ-methacryloxypropyltrimethoxysilane to titanate is 4:
1.
4. A method for preparing modified ultrafine quartz powder according to claim 3, characterized in that: The ambient temperature in the pulverizing chamber is 100-120°C.
5. The method for preparing modified ultrafine quartz powder according to claim 1, characterized in that: In step S3, the pressure-maintaining thermal field adopts a microwave excitation source, and the power of the microwave excitation source is 15KW and the frequency is 2.45GHZ.
6. The method for preparing modified ultrafine quartz powder according to claim 1, characterized in that: In step S4, the gas of the supersonic jet flow is dry steam, nitrogen or argon.
Citation Information
Patent Citations
Superfine active silica powder applied to electronic industry and preparation method thereof
CN113004718A
A method for preparing silica micropowder for epoxy resin systems
CN113308021B
Surface modifier of fused silica powder for copper-clad plate and modification method
CN115678315A
